Inovasi Paket Eduksi dari Limbah Kain Tenun - Rahayu, Maulia; Buana, Charmedtra Bio Angga; Putra, I Gede Yogi Angga Pratama Indra; Arthapala, Lalu Anggir; Wijaya, M Rendi; Anjaini, Baiq Rara Wiwin; Sasmita, M. Tanggap; Hizmi, Surrayal (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
One of the traditional places to make woven fabric is Sukarara Lombok. However, the waste of woven fabric makes changes in management necessary to reduce environmental impact while increasing value. The purpose of this research is to improve skills and awareness about waste and environmental sustainability by using woven fabric waste. To achieve this goal, the methods used include field observations, interviews with weaving craftsmen, and the implementation of socialization and training programs involving employees of weaving craft. In addition, tourist are more interested in local culture and environmental sustainability thanks to this program. This study shows that waste can be used to make creative items such as bracelets and wall hangings, so there is no need to throw them away. The pilot test conducted on tourists received a positive response, most of them found the activity fun and offered a unique experience. The outcome of this activity is that the development of educational products made from woven fabric waste can be one of the attractions of sustainable educational tourism.